4 essays on the sustainable financing of social protection systems of african and latin american countries - (:unkn) unknown (My University, 2021)
Our PhD thesis aims to study the main factors that can influence the sustainable financing of social protection. It is carried out in a context of the willingness of developed as well as developing countries to achieve universal social protection-aim highlighted in the Sustainable Development Goals- without jeopardizing the budget balance.There are studies dealing with this subject that have been realized in the literature. However, they still remain few concerning developing countries notably those on the effect of tax revenues on the social protection financing and on gender inequalities. Our PhD thesis allows us to further the subject by focusing on African and Latin American countries, by using more recent data, by conducting an econometric analysis at an aggregated and disaggregated level of certain explanatory variables and by doing country case studies of South Africa, Uruguay, and Peru.The PhD thesis is constituted of four chapters. The first two deal with the effect of tax revenues on the social protection financing proxied by public expenditures in social protection. Chapter 1 covers 30 African and Latin American countries over the period 2000-2010 and Chapter 2, 9 provinces of South Africa over the period 2002-2017. In both cases, the econometric panel analysis shows that aggregated tax revenues do not have a significant effect on public expenditures in social protection. The results obtained in chapter 1 show that it is “non resource” tax revenues that have a positive and significant effect. Those obtained in chapter 2 show that it is national transfers to provinces that have a positive and significant effect. In particular, it has been observed that it is the Provincial Equity Share component of national transfers that has a positive and significant effect.Chapter 3 deals with the effect of working in the informal sector on access to the main components of social protection in the presence of a policy measure “monotributo” in Urugu
Keywords: African Research